Active Case Search of Kala-azar in an Endemic Area of Bangladesh: - Ghosh, K; Haque, M; Kafi, A; Kabir, S (TAJ: Journal of Teachers Association, 2018)
Visceral Leishmaniasis which is also known as kala-azar is one of the most alarming vector borne Disease in Bangladesh. Kala-azar elimination program was launched in Bangladesh in the year 2008. The primary goal of this program is to decrease the burden of Visceral Leishmaniasis as much as possible. Active case search method are currently using for detection of Visceral Leishmaniasis patient in the community. The successful active case search activity or method lies in preventing and reducing Visceral Leishmaniasis in Bangladesh. The purpose of this study was to assess the Active Case Search activity of Visceral Leishmaniasis Elimination Program in selective endemic area in Bangladesh. This cross-sectional study was conducted within the time frame of 1st January 2016 to 31st December 2016 at different unions of Fulbaria upazila in Mymensingh district using purposive sampling technique according to availability of the respondents and data was collected with pre-tested semi-structured questionnaire by face to face interview. A total number of 111 respondents were enrolled in this study as per selection criteria. Among 111 respondent’s male were 71(64%) and female were 40(36%) and 36 (32.4%) were farmer, 29 (26.1%) were students of different classes, 20 (18%) women were housewife, 11 (9.9%) respondents were in service, 6 (5.4%) were day Laborer and 7 (6.3%) had other profession. Regarding housing status most of them {81(72.98%)} had the kacha housing and only a few respondents {3 (2.7%)} had pakka housing. According to the distance of cowshed or cattle house of the majority of the respondents 95(85.6%) were in the nearest location from living room (Less than 12 feet). Among 111 respondents most of them {78(70.3%)} suffered from kala-azar and 33(29.7%) not suffered from kala- azar in the study area and among these 78 respondents 62(77.5%) found Post kala-azar Dermal Leishmaniasis (PKDL) spot on the body. Most of them 80(72.1%) stated that there was no regular routine visit of the health worker. 90 (81.1%) respondents mentioned that the frequency of Indoor Residual Spray (IRS) was once in a year and 21(18.9%) mentioned 2 times in a year. Among 111 respondents 78(70.27%) mentioned that last supply of Long Lasting Insecticide Net (LLIN) was more than 1 year ago,18(16.22%) mentioned before 6 month and 15(13.51%) before 1 year. This study permits to conclude that Active Case Search Activity of Visceral Leishmaniasis program in Bangladesh facing challenges due to lack of monitoring and supervision. Without strengthening of active case search activity, it is impossible to reach the goal. TAJ 2015; 28(2): 26-39